Reducing Rural Youth Substance Abuse by Educating Parents Through Nontraditional Technology-Based Methods: A Focus On Parental Acceptance of the Online Parenting Wisely Program - Jason A. Gregg (Rural Nurse Organization; Binghamton University, 2012)
Purpose To examine acceptance of technology-based substance abuse prevention programming involving use of the Internet in a rural parent population. Methods Rural parents from a southern state in the east central part of the United States were recruited through local advertisements to participate in two study-related tasks: a brief survey and an online parenting skills educational program entitled Parenting Wisely. Findings Recruitment efforts yielded a total of 39 initial contacts. Of these potential subjects, 25 completed surveys and five requested online program access. Findings demonstrated parents were more likely to indicate a plan to participate in the online program if they cited a primary reason of perceived benefit, whereas parents were more likely to not participate if they selected a lack of time for task commitment as their emphasized motive. Of the five participants who requested online program access, only two of them actually attempted any modules. Neither of them successfully finished any module. Conclusions While rural parents indicated some degree of acceptance to an online parenting educational program through survey responses, those indications did not translate to actual completion of the Parenting Wisely program. Recruitment methods seemed to be most effective with flyer distribution and word-of-mouth social networking strategies, while the cost of newspaper advertisements seemed to greatly outweigh any perceived benefit. Also, the window for potential subject recruitment was most optimal in a four to six week timeline. More research with a larger sample size is needed in order to help identify and validate demographic characteristics leading to increased likelihood of online program participation. In addition, expanded follow-up research is needed to determine as to why parents do or do not complete such programming.  Key Words: Adolescent, Access to Care, Parents, Substance Abuse Prevention, Technology, Rural